2019
DOI: 10.1016/j.bbmt.2018.12.767
|View full text |Cite
|
Sign up to set email alerts
|

Development of Grade II Acute Graft-versus-Host Disease Is Associated with Improved Survival after Myeloablative HLA-Matched Bone Marrow Transplantation using Single-Agent Post-Transplant Cyclophosphamide

Abstract: Post-transplant cyclophosphamide (PTCy) can be used as the sole immunosuppression after myeloablative conditioning (MAC) for HLA-matched bone marrow transplantation (BMT). However, the effects of graft-versus-host disease (GVHD) with this platform are undefined. We retrospectively analyzed 298 consecutive adult patients with hematologic malignancies who engrafted after MAC HLA-matched sibling donor (MSD; n = 187) or HLA-matched unrelated donor (MUD; n = 111) T-cell-replete BMT with PTCy 50 mg/kg on days +3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 41 publications
(40 reference statements)
3
28
0
Order By: Relevance
“…Although greater GVH PS was associated with aGVHD, it did not seem to offer any GVT effect, because the class I GVH PS was not associated with decreased relapse. Previous research by McCurdy et al [63,64] has demonstrated a reciprocal relationship between grade II aGVHD and relapse and progression-free survival in both HLA-matched and haploidentical allo-HCT with PTCy. Given these data, our study might not have been adequately powered to detect an association between PS and incidence of relapse.…”
Section: Discussionmentioning
confidence: 95%
“…Although greater GVH PS was associated with aGVHD, it did not seem to offer any GVT effect, because the class I GVH PS was not associated with decreased relapse. Previous research by McCurdy et al [63,64] has demonstrated a reciprocal relationship between grade II aGVHD and relapse and progression-free survival in both HLA-matched and haploidentical allo-HCT with PTCy. Given these data, our study might not have been adequately powered to detect an association between PS and incidence of relapse.…”
Section: Discussionmentioning
confidence: 95%
“…Importantly, supporting the possible direct clinical relevance of our findings, our results appear fully consistent with clinical outcomes. In human HCT, grade II acute GVHD frequently occurs after PTCy (2,5,(30)(31)(32) and even may be associated with better malignancy control (5,47). Furthermore, high rates of severe acute GVHD are seen when PTCy is used as single-agent GVHD prophylaxis after peripheral blood HLA-matched HCT (48, 49).…”
Section: Discussionmentioning
confidence: 99%
“…These interventions might include post‐transplant administration of targeted therapies, such as demethylating agents (Goodyear, et al , ; Ehx, et al , ; Huls, et al , ). Another strategy for separating GVL effects from severe GVHD in the HLA‐matched transplantation setting might comprise post‐transplantation administration of cyclophosphamide (PTCy, 50 mg/kg on days +3 and +4) as a single GVHD‐prophylaxis agent (Kanakry, et al , ; McCurdy, et al , ).…”
Section: Discussionmentioning
confidence: 99%